Enhancing strength and plasticity by pre-introduced indent-notches in Zr36Cu64 metallic glass: A molecular dynamics simulation study. (15th April 2020) - Feng, Shidong; Li, Lin; Chan, K.C.; Zhao, Lei; Wang, Limin; Liu, Riping
Abstract: The deformation behavior in Zr36 Cu64 metallic glasses with pre-introduced indent-notches has been studied by molecular dynamics simulation at the atomic scale. The indent-notches can trigger the formation of densely-packed clusters composed of solid-like atoms in the indent-notch affected zone. These densely-packed clusters are highly resistant to the nucleation of shear bands. Hence, there is more tendency for the shear bands to nucleate outside the indent-notch affected zone, which enlarges the deformation region and enhances both the strengthening effect and the plastic deformation ability. For indent-notched MGs, when determining the initial yielding level, there is a competition process occurring between the densely-packed clusters leading to the shear band formation outside the indent-notch affected zone and the stress-concentration localizing deformation around the notch roots. When the indent-notch depth is small, the stress-concentration around the notch root plays a dominant role, leading to the shear bands initiating from the notch root, reminiscence of the cut-notches. As the indent-notch depth increases, there are many densely-packed clusters with high resistance to deformation in the indent-notch affected zone, leading to the shear band formation from the interface between the indent-notch affected zone and the matrix. Current research findings provide a feasible means for improving the strength and the plasticity of metallic glasses at room temperature.